2019
DOI: 10.1002/ange.201813439
|View full text |Cite
|
Sign up to set email alerts
|

A Guiding Principle for Strengthening Crosslinked Polymers: Synthesis and Application of Mobility‐Controlling Rotaxane Crosslinkers

Abstract: Three component mobility controlling vinylic rotaxane crosslinkers with two radically polymerizable vinyl groups (RC_Rs) were synthesized to prove that the mobility of the components of the RC_Rsp laysacrucial role in determining the properties of rotaxane-crosslinked polymers (RCPs). RC_Rs( R= H, Me,o rE t) were obtained from living ringopening polymerization. RCP_Et was prepared using RC_Et, which exhibits the lowest component mobility.T he low component mobility is reflected in inferior mechanical strength … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…[ 37,38 ] They also synthesized various rotaxane‐crosslinked polymers using crown‐ether‐containing vinylic rotaxane crosslinkers in nonaqueous systems. [ 39–41 ] Coskun and co‐workers discovered an interesting application by introducing polyrotaxane into poly(acrylic acid) as a highly elastic binder to improve the cycling stability of Li‐ion battery electrodes. [ 42 ] These sophisticated efforts represent significant steps in mechanical bond chemistry toward the practical application of elastomers, also called as molecular pulley.…”
Section: Figurementioning
confidence: 99%
“…[ 37,38 ] They also synthesized various rotaxane‐crosslinked polymers using crown‐ether‐containing vinylic rotaxane crosslinkers in nonaqueous systems. [ 39–41 ] Coskun and co‐workers discovered an interesting application by introducing polyrotaxane into poly(acrylic acid) as a highly elastic binder to improve the cycling stability of Li‐ion battery electrodes. [ 42 ] These sophisticated efforts represent significant steps in mechanical bond chemistry toward the practical application of elastomers, also called as molecular pulley.…”
Section: Figurementioning
confidence: 99%
“…41 The correlation peaks between the CD 3 and CD 5 protons of β-CD and −CH 3 in the isopropyl groups of PNIPAAm were clearly observed in F40N4CD, just as in an IC formed between PNIPAAm and β-CD and the self-assembly of β-CDs with P(NIPAAm-co-HEAc). 29,30 It is also worth noting that despite the chemical shifts overlapping with the signals of H 3 and H 5 protons of β-CD in the 1 H NMR spectrum, the abovementioned correlations could also have originated from the CD 2 and CD 4 protons, which are located outside the CD cavity because of the presence of free β-CDs. Although the correlation between the CD 3 and CD 5 protons of β-CD and those of Fc in the central initiator block was not seen due to its low molar fraction in the polymeric chain, this analysis provided further evidence to corroborate the successful selfassembly of the PNIPAAm homo-and copolymers with β-CDs to construct PPRs.…”
Section: The Journal Of Physical Chemistry Bmentioning
confidence: 99%
“…This unique architecture could attenuate the intermolecular hydrogen-bond interactions of neighboring γ-CDs threaded onto the polymeric chains and would bestow the resulting PPRs and PRs a fantastic damping behavior from the "molecular friction" viewpoint, showing great potential as novel, intelligent, and functional materials. 29 As a novel thermoresponsive polymer, the self-assembly of PNIPAAm with β-CDs and the impact of this self-assembly on the cloud point (CP) of PNIPAAm in aqueous solution also brought concerns. For example, Han, et al observed that the formation of an inclusion complex (IC) between PNIPAAm and β-CD can increase the CP up to about 57 °C, whereas that in the PNIPAAm/β-CD physical blend is only about 33 °C.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cross-linking performances of the polymers can be reversible or irreversible relying on the nature of the crosslinking [4]. The chemical method is irreversible; however, the physical and the biological are reversible by the application of stress, electricity, light, pressure, changing pH or magnetic field [5]. Conventional techniques of polymerization such as the condensation and the free-radical polymerizations were used mainly for preparation of chemically cross-linked polymers [6].…”
Section: Introductionmentioning
confidence: 99%